Firm specific determinants of markup ‐ the case of Slovenian manufacturing firms - Ponikvar, Nina; Rant, Melita (Journal of Business Economics and Management, 2007)
Investigations of firms’ pricing decisions and performances have been twofold. While within the industrial organisation framework stress is placed on industry‐specific factors and the market power of firms within industries, various organisational theories emphasise the role of ‘soft’ factors in the determination of firms’ performance. The main thesis of our paper is that the size of a firm’s markup can mostly be explained by the firm’s productivity, capital and labour costs, as well as the firm’s market power and organisational structure characteristics, when the external environment and industry membership is controlled for. Our objective is thus to explain firm‐level markups by a set of firm‐specific factors. The empirical analysis of markup determinants is based on a sample of Slovenian manufacturing firms (NACE 15–37) in the 1994–2003 period, applying panel data regression GLS model and ANOVA analyses. We find that, besides market share and cost factors, organisational structure change occurring after some threshold significantly increases markups. First Published Online: 14 Oct 2010